Models of gouty nephropathy: exploring disease mechanisms and identifying potential therapeutic targets - Wang, Lin; Zhang, Xiaoyu; Shen, Jiayan; Wei, Yuanyuan; Zhao, Ting; Xiao, Niqin; Lv, Xiaoman; Qin, Dongdong; Xu, Yundong; Zhou, Yang; Xie, Jing; Li, Zhaofu; et al. (Frontiers in Medicine, 2024)
Gouty nephropathy (GN) is a metabolic disease with persistently elevated blood uric acid levels. The main manifestations of GN are crystalline kidney stones, chronic interstitial nephritis, and renal fibrosis. Understanding the mechanism of the occurrence and development of GN is crucial to the development of new drugs for prevention and treatment of GN. Currently, most studies exploring the pathogenesis of GN are primarily based on animal and cell models. Numerous studies have shown that inflammation, oxidative stress, and programmed cell death mediated by uric acid and sodium urate are involved in the pathogenesis of GN. In this article, we first review the mechanisms underlying the abnormal intrinsic immune activation and programmed cell death in GN and then describe the characteristics and methods used to develop animal and cell models of GN caused by elevated uric acid and deposited sodium urate crystals. Finally, we propose potential animal models for GN caused by abnormally high uric acid levels, thereby provide a reference for further investigating the methods and mechanisms of GN and developing better prevention and treatment strategies.